Morphology of copper deposits obtained by metallic electrodeposition - González Mercado, Griselda V.; González , Carlos J.; Oliva , Marcos I.; Brunetti, Verónica; Eimer, Griselda A. (Elsevier, 2015)
Electrochemical deposition of copper from copper nitrate aqueous electrolyte on graphite substrate was investigated at current densities between 0.03 mA/cm2 - 1.36 mA/cm2 and in the voltage range of 3 V to 15 V. The surface morphology and elemental composition of the resultant deposit were characterized by electron microprobe analysis (EMPA). These images illustrate the influence of current density on the shape of copper electrodeposited on the electrode surface. Rods, polyhedral bodies, pentagonal pyramids, dendritics, spiked spheres or cauliflower-like shapes are observed depending on the electrodeposition conditions.
Keywords: EMPA; Superficial morphology; Copper